Effect of the Mineralizer Solution in the Hydrothermal Synthesis of Gadolinium-Doped (10% mol Gd) Ceria Nanopowders. Issue 2 (May 2016) - Dell'Agli, Gianfranco; Spiridigliozzi, Luca; Marocco, Antonello; Accardo, Grazia; Ferone, Claudio; Cioffi, Raffaele
Background: Gadolinium-doped ceria is an attractive electrolyte material for potential application in solid oxide fuel cells (SOFCs) operating at intermediate temperatures typically with 10%-20% substitution of Ce +4 by Gd +3 . In particular, 10% gadolinium-doped ceria seems to have the highest values of conductivities among the other dopant compositions. Methods: Nanosized powders of gadolinium-doped ceria were prepared by hydrothermal treatment using coprecipitate as a precursor and in the presence of 3 different mineralizer solutions. The powders obtained were characterized by X-ray diffraction analysis, scanning electron microscopy, transmission electron microscopy and thermal analysis, while the electrical behavior of the corresponding pellets were ascertained by AC impedance spectroscopy. Results: Nanocrystalline gadolinium-doped ceria powders with fluorite cubic crystal structure were obtained by hydrothermal treatment. Independent of the mineralizer used, these powders were able to produce very dense ceramics, especially when selecting an optimized sintering cycle. In contrast, the electrical behavior of the samples was influenced by the mineralizer solution, and the samples synthesized in the neutral and alkaline solutions showed higher values of electrical conductivity, in the range of temperatures of interest. Conclusions: By the coprecipitation method, it has been possible to synthesize nanosized gadolinium-doped cerium oxide in a fluorite structure, stable in a wide range of temperatures. Hydrothermal treatment directly on the as-synthesized coprecipitates, without any drying step, had a very positive effect on the powders, which can be sintered with a high degree of densification, especially with an optimized sintering cycle. Furthermore, the electrical behavior of these samples was very interesting, especially for the samples synthesized using neutral mineralizer solution and basic mineralizer solution.